Walter Herron Taylor correspondence - Taylor, Walter Herron, 1838-1916.
Letter from Taylor, aide-de-camp to Gen. Robert E. Lee, addressed to Lieut. Gen. Richard Heron Anderson, regarding military strategy of the Confederate army.
Confederate army officer and banker of Norfolk, Va.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Anderson, Richard Heron, -- 1821-1879 -- Correspondence; Lee, Robert E. -- 1807-1870.; Confederate States of America. -- Army; United States -- History -- Civil War, 1861-1865.; Army officers, Confederate